Mengubah Laut Menjadi Kesempatan: Pengembangan Usaha Keripik Kertas Rumput Laut - Hidayat, Nurul; Amanda, Allesandra Dior; Salwa S, Agustina Neesha; Azhar A, A. Rezki Hidayat Ryan; Felicia, Rusdianti Lutfiah Adeline; Dewi S, Elyza (Sahabat Publikasi, 2024)
This community service journal aims to find out how to process seaweed so that it can become a product that has selling value. This research involved an UMKM person who has the ability in the field of seaweed processing. Through a series of training and mentoring, we were taught how to process seaweed into a product that has a selling value, namely “kringkel”. Kringkel is a product whose main raw material is seaweed. Other raw materials used in this product are glutinous rice flour, cheese, vanilla, sugar, salt, milk, and eggs. Kringkel has a crunchy texture and has a savory and salty taste from the cheese. Kringkel is also included in the typical souvenirs of Tarakan. In making kringkel, there are influencing factors such as the quality of seaweed used, the amount of ingredients, the frying temperature, the right way to fry when the dough has been put into the pan, and how to package. The result of this service is that the community can utilize the resources around them to be able to create new business opportunities that are beneficial personally and to the people around them. This not only increases their income, but also encourages economic independence.